Evaluasi Pembelajaran Dikelas (International Forum of Researchers and Lecturers, 2023)
This research aims to determine the evaluation of learning in class. The research approach used in this study is a qualitative approach. This research is qualitative in nature where the main problem in this research is about the evaluation of classroom learning. The method used in this research is the literature method in which this method uses topics from certain research that support a specific identification of research questions, as well as processing research material from researchers and from books that have been published or which have been researched. From the data analysis it is known that evaluation of learning in class is a process for determining the value of learning and learning carried out, through assessment activities or measuring learning and learning.